2021
DOI: 10.1016/j.jes.2020.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Changes in air pollution during COVID-19 lockdown in Spain: A multi-city study

Abstract: Highlights Variations in air quality in terms of CO, SO 2 , PM 10 , O 3 and NO 2 levels were studied. The lockdown of Spain was not able to reduce severe air pollution in all its forms. Significant reductions of NO 2 levels were achieved in most cities. Increases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
140
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(167 citation statements)
references
References 45 publications
22
140
3
2
Order By: Relevance
“…We have recently demonstrated that the Spanish lockdown did not decrease air pollution (NO2, CO, SO2, and PM10 ) considering meteorological factors on the pollutants' levels (Briz-Redón et al, 2020). Furthermore, the O3 levels were generally increased during this period.…”
Section: Introductionmentioning
confidence: 82%
“…We have recently demonstrated that the Spanish lockdown did not decrease air pollution (NO2, CO, SO2, and PM10 ) considering meteorological factors on the pollutants' levels (Briz-Redón et al, 2020). Furthermore, the O3 levels were generally increased during this period.…”
Section: Introductionmentioning
confidence: 82%
“…Adicionalmente, a raíz de las investigaciones presentadas, surge la necesidad de evaluar los contaminantes atmosféricos considerando los factores meteorológicos (60) . En particular, Tosepu et al (61) analizaron que el nivel medio diario de las concentraciones de O3 fue positivo correlacionado con la temperatura promedio diaria, corroborado por Dantas et al (28) , quienes consideran que las altas temperaturas y los índices de radiación solar favorecen la formación de ozono.…”
Section: Impacto De La Meteorologíaunclassified
“…These measures, aimed at containing the virus spread [1923], have focused on social distancing and population confinement, as well as the cease of non-essential productive and social activities. Overall, the measures have contributed to a global diminishing of human activities [24]. This abrupt and dramatic disruption of most human social and economic activities have already had quantifiable effects on urban environments by marked reductions in air pollution [2527] and noise [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most noticeable and generalized measure has been applying certain degree of population lockdown, which renders our city streets empty and virtually silent. This situation provides a once-in-a-lifetime opportunity to study urban wildlife responses to less active, noisy and polluted cities and gain unprecedented mechanistic insights into how human activities affect wildlife [24,30,31]. Product of the human lockdown, unusual observations of animals in urban areas worldwide have flooded the media and the internet planting in the social imaginary the idea that “nature is getting back its space” ( sensu [32]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation